Bardet Biedl Syndrome - Ghosh, Taraknath; De, Sangita; Pati, Sananda; Kumar, Prabhat; Chaki, Bhusan (Journal of Nepal Paediatric Society, 2013)
This is a case report of Bardet-Biedl syndrome, diagnosed in a 8 year old girl presented with obesity. She had polydactyly, mild mental retardation, retinitis pigmentosa in both eyes, with hypoplastic uterus, fallopian tube and ovaries. She was born to a consanguinous marriage and had a family member with same features. DOI: http://dx.doi.org/10.3126/jnps.v33i2.7359 J Nepal Paediatr Soc. 2013; 33(2):129-131